Milk intake during pregnancy is inversely associated with the risk of postpartum depressive symptoms in Japan: the Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Okubo, Hitomi; Sasaki, Satoshi; Furukawa, Shinya; Arakawa, Masashi (Nutrition research (New York, N.Y.), 2016)
Only one epidemiologic study has investigated the association between dairy product intake during pregnancy and postpartum depressive symptoms. Epidemiologic evidence on the relationships between calcium and vitamin D intake during pregnancy and postpartum depressive symptoms is also lacking. The present prospective study examined these issues in Japan. Study subjects were 1319 women. During pregnancy, dietary intake during the preceding month was assessed using a self-administered diet history questionnaire in the baseline survey. Postpartum depressive symptoms were defined as present when subjects had an Edinburgh Postnatal Depression Scale score of 9 or higher between 3 and 4 months postpartum. Adjustment was made for age, gestation at baseline, region of residence, number of children, family structure, history of depression, family history of depression, job type, education, body mass index, having smoked during pregnancy, cesarean delivery, baby's sex, baby's birth weight, and total energy intake. After adjustment for the confounding factors, compared with milk intake in the lowest quartile, intake levels in the second and fourth quartiles were independently associated with a reduced risk of postpartum depressive symptoms, although the inverse exposure-response relationship was not significant: the adjusted odds ratio between extreme quartiles was 0.51 (95% confidence interval, 0.28-0.93; P for trend = .12). No material relationships were observed between intake of total dairy products, yogurt, cheese, calcium, or vitamin D and the risk of postpartum depressive symptoms. The present prospective cohort study in Japan suggests that higher milk intake during pregnancy is associated with a reduced risk of postpartum depressive symptoms.